Adoption of UTAUT3 Model on the Use of BSI Mobile Application - Putri, Daneza Dhea Ananda; Sukardi, Budi (Institut Agama Islam Negeri Madura, 2025)
This research is used to examine the variables that determine user intention in adopting BSI Mobile services as a digital payment platform through the UTAUT3 construct model. This type of research is quantitative, with a research sample of 245 respondents as the primary data source using a questionnaire survey. Data analysis using SmartPLS software. The research findings show that there are variables that have a significant influence, namely the variables of performance expectations, social influence, habits, and personal innovation on behavioural intentions, as well as facilitating conditions, habits, and behavioural intentions on usage behaviour. Meanwhile, variables that do not have a significant impact are effort expectations, hedonic motivation, price value, and facilitating conditions on behavioural intention, as well as personal innovation on usage behaviour. This research contributes to knowing the link between how the behaviour of BSI Mobile service users as a guide for platform owners and users to develop better services and the Indonesian people in choosing the use of digital payments, as well as spreading the literacy of using the BSI Mobile application. Keywords: UTAUT3; BSI Mobile; SEM-PLS. Abstrak: Penelitian ini digunakan untuk mengkaji variabel penentu niat pengguna dalam mengadopsi layanan BSI Mobile sebagai platform pembayaran digital melalui model konstruk UTAUT3. Jenis penelitian ini adalah kuantitatif, dengan sampel penelitian sejumlah 245 responden sebagai sumber data primer menggunakan survei kuesioner. Analisis data menggunakan software SmartPLS. Temuan penelitian menunjukkan bahwa terdapat variabel yang memiliki pengaruh signifikan yaitu variabel harapan kinerja, pengaruh sosial, kebiasaan, dan inovasi pribadi terhadap niat berperilaku, serta kondisi yang memfasilitasi, kebiasaan, dan niat berperilaku terhadap perilaku penggunaan. Sedangkan variabel yang tidak memiliki dampak signifikan yaitu harapan usaha, motivasi hedonis, nilai harga, dan kondisi yang memfasilitasi terhadap niat berperilaku, serta inovasi pribadi terhadap perilaku penggunaan. Penelitian ini berkontribusi untuk mengetahui kaitan antara bagaimana perilaku pengguna layanan BSI Mobile sebagai panduan untuk pemilik platform maupun pengguna untuk mengembangkan layanan yang lebih baik serta masyarakat Indonesia dalam memilih penggunaan pembayaran secara digital, sekaligus menyebarkan literasi penggunaan aplikasi BSI Mobile. Kata Kunci: UTAUT3; BSI Mobile; SEM-PLS.